2015
DOI: 10.32637/orli.v45i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh N–asetilsistein terhadap transpor mukosilia tuba Eustachius penderita otitis media supuratif kronis tanpa kolesteatoma

Abstract: Latar belakang: Otitis Media Supuratif Kronik (OMSK) adalah radang telinga tengah dengan perforasi membran timpani dan keluarnya sekret lebih dari 2 bulan. Pengobatan OMSK saat ini masih belum memuaskan. Peneliti mengharapkan dengan kelebihan dari N–asetilsistein (NAC) dapat memperbaiki transpor mukosilia tuba Eustachius. Tujuan: Penelitian ini bertujuan membandingkan waktu transpor dan penurunan waktu transpor mukosilia tuba Eustachius penderita OMSK tanpa kolesteatoma sebelum dan setelah diberikan pengobatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Otorrhoea is the most common complaint in this study because the inflammatory process will affect the middle ear mucociliary transport system where goblet cells increase so that mucus production will also increase. Chao et al in Sari et al reported that the anterior two thirds of the Eustachian tube had the most active mucociliary transport activity (17). Based on the length of suffering CSOM, it was found that CSOM 1-5 years were 8 patients (50%) and >5 years were 8 patients (50%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Otorrhoea is the most common complaint in this study because the inflammatory process will affect the middle ear mucociliary transport system where goblet cells increase so that mucus production will also increase. Chao et al in Sari et al reported that the anterior two thirds of the Eustachian tube had the most active mucociliary transport activity (17). Based on the length of suffering CSOM, it was found that CSOM 1-5 years were 8 patients (50%) and >5 years were 8 patients (50%).…”
Section: Discussionmentioning
confidence: 98%
“…This is in line with this study, it was found that patients with active phase safe type CSOM who had the most ear complaints were otorrhoea as many as 9 people (56.3%) and hearing loss as many as 5 people (31.3%) followed by complaints of tinnitus as many as 1 person (6.3%) and ear pain as much as 1 person (6.3%).While suffering from CSOM, an inflammatory process occurs that releases various inflammatory mediators. This process due to the proinflammatory cytokines TNF-, IL1-ß, and IL-8 play an important role in mucus production by middle ear goblet cells, then caused mucociliary dysfunction in the middle ear, mucus build up and ultimately decrease mucociliary transport in the tube Eustachius (17).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on N-acetylcysteine (NAC) because most COVID-19 patients had severe pneumonia with excess mucus in the respiratory tract (Ochs et al, 2012;Sari et al, 2015;Yuliana, 2020). The usual dose of NAC in pneumonia is (3x200 mg) po, used as a mucolytic agent.…”
mentioning
confidence: 99%
“…It is also supported by evidence-based medicine research journals, which in practice at the hospital is used N-Acetylcysteine at a dose of 5 grams per day intravenously given in 500 ml PZ infusion over 6-8 hours. In addition, in the COVID-19 Hospital Clinical Practice Guidebook, Dr. Soetomo Surabaya, high dose of N-Acetylcysteine (NAC) 5 grams per day given in 500 ml NaCl 0.9% or Dextrose 5% intravenous drip 4 hours (Damayanti & Ryusuke, 2017;Sari et al, 2015Sari et al, , 2017. SARS-CoV-2 infection is associated with an imbalance of oxidants and antioxidants, resulting in inflammation and tissue damage (Damayanti and Ryusuke, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation